Research on the Role of Combined Chemotherapy and Radiotherapy in Patients With N+ Non-Metastatic Metaplastic Breast Carcinoma: A Competing Risk Analysis Model Based on the SEER database, 2000 to 2015 - Ma, Yifei; Yang, Zejian; Gao, Yihan; Li, Kunlong; Qiu, Pei; Chen, Heyan; Pu, Shengyu; Wang, Bo; Zhou, Can (Frontiers in Oncology, 2021)
Purpose: Due to the rarity of metaplastic breast carcinoma (MpBC), no randomized trials have investigated the role of combined chemotherapy and radiotherapy (CCRP) in this condition. We aimed to explore and identify the effectiveness of CCRP in patients with regional lymph node metastasis (N+) non-metastatic MpBC. Materials and Methods: Data were obtained from the National Cancer Institute’s Surveillance, Epidemiology, and End Results (SEER) Program database. We assessed the effects of CCRP on overall survival (OS), breast cancer-specific survival (BCSS), and breast cancer-specific death (BCSD) using Kaplan‐Meier analysis, competing risk model analysis, and competing risk regression mode analysis. Results: A total of 707 women and 361 death cases were included in the unmatched cohort, of which 76.45% (276/361) were BCSD, and 23.55% (85/361) were non-breast cancer-specific deaths (non-BCSD). Both the ChemT and CCRP groups had better OS (ChemT group: HR: 0.59, 95% CI: 0.45-0.78, P<0.001; CCRP group: HR: 0.31, 95% CI: 0.23-0.41, P<0.001) and BCSS (ChemT group: HR: 0.63, 95% CI: 0.45-0.87, P<0.001; CCRP group: HR: 0.32, 95%CI: 0.22-0.46, P<0.001) than the non-therapy group. Subjects in the CCRP group tended to have significantly lower cumulative BCSD (Gray’s test, P=0.001) and non-BCSD (Gray’s test, P<0.001) than the non-therapy group or ChemT group. In competing risk regression model analysis, subjects in the CCRP group had a better prognosis in BCSD (HR: 0.710, 95% CI: 0.508-0.993, P=0.045) rather than the ChemT group (HR: 1.081, 95% CI: 0.761-1.535, P=0.660) than the non-therapy group. Conclusion: Our study demonstrated that CCRP could significantly decrease the risk of death for both BCSD and non-BCSD and provided a valid therapeutic strategy for patients with N+ non-metastatic MpBC.